The roles of an urban rooftop garden for the staff of a memory clinic - a qualitative post-occupancy evaluation - Oher, Nina; Bengtsson, Anna; Grahn, Patrik (Frontiers in Psychology, 2025)
The world is experiencing an acute global shortage of healthcare staff, with health and well-being issues, recruitment and retention difficulties. Strategies with potential to improve staff well-being are therefore receiving increasing attention. Contact with nature in the workplace has been shown to help staff recover, reduce stress levels and increase job satisfaction. Additionally, rooftop gardens have become a trend due to the world’s growing urbanization and densification of cities. The aim of the study was therefore to explore the role of an urban rooftop garden for staff at a Memory Clinic, with a specific focus on the physical and health-promoting aspects of the garden. A post-occupancy evaluation (POE) was conducted using qualitative research methodology and focus group interviews, including nine participants (divided into a management – and a staff team) and a total of five interviews. Thematic analysis was used for the transcribed interviews. The evaluation spanned a full year to capture the use, experience and meaning of the rooftop garden in all seasons and possible weather conditions. Three overarching themes and associated sub-themes were identified. The first one, (1) The rooftop garden as a place of Use, promoted both (a) Spontaneous Visits and (b) Organized Activities. The second theme, (2) The rooftop garden as a place to Experience the World Outside, offered (a) Contact with Nature and Surrounding Life and a sense of being (b) Beyond Hospital Walls. The final theme, (3) The rooftop garden as a place of Meaning for Well-Being and Work Life Sustainability, was linked to being either (a) Positive and Rewarding or linked to (b) Temporary wishes and needs for support. Each sub-theme was connected to physical features in the environment, as well as locations (zones) in the garden, which produced results with design significance and potential for practical application and use in planning contexts. The results furthermore show that an outdoor environment such as a rooftop garden can include both salutogenic and pathogenic strategies and therefore be used to both promote health and prevent ill health for staff, that is, provide conditions for optimal support and promotion of health and well-being. Finally, the study highlights urban rooftop gardens as a type of garden with potentially unique, positive and beneficial properties due to its combination of expansive views and urban feel, with calmness, safety, privacy and enhanced seasonal and natural impressions – something that is considered difficult to achieve in an urban hospital garden at ground level.